Review: Wharton’s Jelly MSCs Secretome as a Neurodegenerative Therapeutic Approach - Iis Nur Azizah; Muhammad Novrizal Abdi Sahid; Retno Murwanti (Majalah Farmaseutik, 2026)
Wharton’s Jelly Mesenchymal Stem Cells (WJMSCs) have great potential in regenerative therapy, mainly because their secretome is rich in bioactive molecules. WJMSCs secretome plays a role in the treatment of various neurodegenerative diseases, such as Alzheimer’s Disease (AD), Parkinson’s Disease (PD), Amyotrophic Lateral Sclerosis (ALS), and Multiple Sclerosis (MS). This journal review aims to analyze the therapeutic potential of Wharton’s Jelly Mesenchymal Stem Cells (WJMSCs) secretome in treating various neurodegenerative diseases. Literature searches were conducted through electronic databases such as Elsevier, Google Scholar, PubMed, Science Direct, and Springer Link. Based on the review conducted, data obtained that in AD, this secretome reduces oxidative stress, increases neurogenesis, and inhibits β-amyloid toxicity. In PD, WJMSCs protect dopaminergic neurons, increase dopamine levels, and improve motor function. For ALS, WJMSCs secretome reduced inflammation and increased neurotrophic factors, while MS supported remyelination and neuroprotection. With these benefits, WJMSC secretome has the potential to be an innovative therapy for neurodegenerative diseases, although further clinical studies are needed.